Analisis Pengendalian Mutu Produk Rendang Domba di CV. Mitra Tani Farm Menggunakan Checksheet, Diagram Pareto, dan Diagram Fishbone - Kharimatussalma Kharimatussalma; Rachelin Chelsea Januar; Nanda Cahyani Tunang; Manik Liraqyeti; Rafiq Hariri; Naila Lupita Tambunan; Muhamad Dava Alfarezi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the quality control of lamb rendang products at CV. Mitra Tani Farm using three Statistical Quality Control (SQC) tools: the checksheet, Pareto diagram, and Fishbone diagram. The research was conducted to identify major product defects and their root causes in the canned lamb rendang production process. A descriptive quantitative method was applied through direct observation, interviews, and documentation. Data were collected using a checksheet to record defect types and frequencies, then analyzed with Pareto and Fishbone diagrams to determine dominant issues and underlying factors. The results showed that labeling errors were the most frequent defect, followed by inaccurate sterilization and machine overload. These problems were mainly caused by limited operator skills, non-standardized procedures, and inadequate machine performance. The findings indicate that improving operator training, refining standard procedures, and maintaining equipment are essential to enhance product quality and consistency.